التفريق بين الزوجين بسبب الضرر في القانون والعرف الأفغاني : دراسة فقهية تحليلية - عزيزي، عبد البصير (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This thesis deals with a study of the reasons for the separation between spouses due to harm according to Afghan customs and civil law. This study aims to explain the harms that cause separation between spouses, and the extent of the damages on marital life. This study is based on three methods: inductive, analytical, and field survey through interviews with scholars, judges, and lawyers in Shariah courts. This study has reached several conclusions, the most important of which is that the Afghan civil law does not specify clear limits to the concept of harm and its conditions, nor does it specify its restrictions but leaving it to the court's judgment and its ability to deal with cases of harm and harmful acts. For example: some of them say that defects are among the reasons for separation due to harm, and others say that absence and inability to provide basic needs (Nafaqah) are among the reasons for separation due to harm. Hence, the researcher recommends an amendment of provisions dealing with judicial separation due to harm.